Dakwah Kultural dan Dakwah Yang Ramah: Rancangan Komunikasi untuk Dakwah - HM. Kholili (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
The teachings of Islam as mercy, need a proper dakwahand should perform a social observation. In this step Berlo requires a preacher as communicators must have: the ability to communicate, the ability of knowledge and ability to understand the socio-cultural community.Thought development concept of dakwah shall be carried out measurements in the field that the results show that a preacher should perform the following steps: 1). Start with an effort to understand a community's culture and then try to adjust to the culture of the people. 2). Based on the ability to understand and adapt to the culture of the people, a preacher will be able to communicate better. 3). Based on the communication skills of a preacher will acquire knowledge about the condition of the society memadahi.Based on these findings cultural dakwah must be made, that is that forthwith proselytizing dakwah messages in accordance with the actual needs of community and submit it to the